PENGARUH PENGGUNAAN TEKNIK THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS TEKS CERITA ULANG BIOGRAFI SISWA KELAS X SMA NEGERI 14 PADANG - Nursaid, Tifani, Atmazaki, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study consists of three things. The first, to descripe the skills of rewriting biograpy text without using think talk write (TTW) technique of student class X Senior High School 14 Padang. The second, to describe the skills of rewriting biography text using think talk write (TTW) technique of student class X Senior High School 14 Padang. The third, to analyze the influence of using think talk write (TTW) technique of student class X Senior High School 14 Padang. Based on the research it is known that there are three following things. The first, the skils of rewriting  biography text without using think talk write (TTW) technique of student class X Senior High School 14 Padang is in more than enough qualification (MtE)  in average 70,31. The second, the skills of rewriting biography text using think talk write (TTW) technique of student class X Senior Hihg School 14 Padang is in good qualification (G) in average 78,30. The third, based on the uji-t research, hyphothesis alternative (H1) is accepted at the level of trust 95% and degrees of freedom (df) = n-2 due tcount  > ttable(3,02 > 1,70). Kata kunci: pengaruh, teknik think talk write (TTW), teks cerita ulang biografi